Valuers’ and Valuation Firms’ Characteristics as Causes of Inaccuracy in Valuation in Nigeria - Babawale, G. K.; Omirin, M. M. (Mediterranean Journal of Social Sciences, 2011)
Studies in a number of countries have identified certain factors as major contributors to inaccuracy in real property valuation.Of these, individual characteristics of valuers and to a lesser degree, the ethical culture of the firms that engage them, are foremost anduniversal. This study evaluates the predictive and relative importance of individual characteristics of valuers/valuation firms thatcontribute to inaccuracy in residential property valuation in Lagos, Nigeria. It also includes the results of an empirical study on the levelof accuracy achieved by valuers in the study area. Information elicited from senior partners of 250 firms of Estate Surveyors and valuers(appraisers) operating within Lagos metropolis were analyzed using both descriptive and inferential statistics. The study revealed a degreeof inaccuracy that is beyond the industry’s tolerance limits. The study also identified the experience and exposure of valuers; the number ofvaluations undertaken by valuers within a period of time; professional status of valuers; valuers’ familiarity with relevant markets; andinterestingly, the gender of valuers, in that order, as factors that significantly contribute to inaccuracy in residential property valuation inthe study area. The paper prescribes, among others, quality assurance measures, and a more proactive regulatory framework, as immediatemeasures required to curb complacency and excesses among valuers and valuation firms in the study area.